Open Reduction and Internal Fixation of Mandibular Fracture without Rigid Maxillomandibular Fixation - El-Anwar,Mohammad Waheed (2015)
Introduction The ability to treat fracture with open reduction and internal fixation (OR/IF) has dramatically revolutionized the approach to mandible fracture. With OR/IF, the postoperative role of rigid maxillomandibular fixation (MMF) has declined, but it is used to maintain proper occlusion until internal fixation of the fracture is achieved. Objective To assess intraoperative manual MMF during OR/IF of selected cases of mandibular fractures. Methods This prospective study was conducted on 80 patients with isolated mandibular fractures managed by OR/IF using two titanium miniplates. The patients were classified into two groups: a control group (40 patients) treated by OR/IF after intraoperative rigid MMF followed by immediate MMF removal, and a study group (40 patients) treated by rigid MMF, which was replaced by temporary intraoperative manual MMF (3MF) until plate fixation. Results There were no significant differences of the postoperative complication and dental occlusion, although a highly significant reduction of operative time was achieved in the 3MF group. Patient who received the 3MF technique had statistically significantly better average intrinsic vertical mouth opening in the early postoperative period (1 week after surgery), and normal mouth opening could be achieved in all cases in both groups 8 weeks after surgery. Conclusions Intraoperative rigid MMF is not mandatory and can be replaced in selected cases of fracture mandible by manual maintenance of proper dental occlusion until hardware fixation, gaining the advantages of shorter operative time and less risk of blood-transmitted diseases to the surgical team and the patient in addition to the benefits of immediate postoperative mandible mobilization.